How Do I Love Thee? Let Me Count the Js Implicit Egotism and Interpersonal Attraction. (article). - Jones, John T.
From the perspective implicit egotism people should gravitate toward others who resemble them because similar others activate people's positive, automatic associations about themselves . Four archival studies and 3 experiments supported this hypothesis. Studies 1-4 showed that people are disproportionately likely to marry others whose first or last names resemble their own . Studies 5-7 provided experimental support for implicit egotism. Participants were more attracted than usual to people (a) whose arbitrary experimental code numbers resembled their own birthday numbers, (b) whose surnames shared letters with their own surnames, and (c) whose jersey number had been paired, subliminally , with their own names. Discussion focuses on implications for implicit egotism, similarity, and interpersonal attraction. -- (from the author).
Keywords: Psychology-Periodicals.